Impact Evaluation of a Social Franchise Model for Improving Infant and Young Child Feeding and Child Nutrition in Vietnam - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
Alive & Thrive is an initiative that aims to improve infant and young child feeding practices and reduce childhood stunting. In Vietnam, Alive & Thrive's primary intervention is implemented through a social franchise linked with the government's health system. The impact evaluation is conducted using a cluster-randomized design in which 20 commune health centers (CHC) were assigned to the social franchise model, and 20 CHC were assigned to routine government services. Repeated cross-sectional baseline and endline surveys will be used to assess the public health impact of this intervention. The baseline was in 2010 and an endline survey in the same communities will be conducted in 2014. Mixed methods process evaluation will be conducted in 2011, 2012 and 2013 to study the pathways through which the program impact is achieved.